PENGARUH STRATEGI PEMBELAJARAN LEARNING CYCLE DAN LOCUS OF CONTROL SISWA TERHADAP HASIL BELAJAR IPA - Bambang Joko Surya (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2018)
: This study aims to determine: (1) Differences biology student learning outcomes that dibelajarkan with learning strategies Learning Cycle better than students who study with strategei conventional learning, (2) The difference of students who have internal locus of control to obtain the results of studying biology better of the students who have external locus of control, (3) Interaction between learning strategies and locus of control in giving effect to biology students' learning outcomes. The research was conducted in the Junior School I Binjai. The population of this study are all eighth graders Binjai SMP Negeri 1 212 people. Samples were taken with a random cluster technique samplig and further through the draw, the class VIII was selected as the class-2 treated with the learning strategies and classroom Learning Cycle VIII-3 was chosen as the class that were treated with conventional pembelajara. Locus of Control Data was collected using a questionnaire and data with the test results to study Biology.Instruments used after validated by the validator and test instruments. The test results show the distribution of the data requirements for learning outcomes Biology and Locus of Control is the normal distribution and homogeneous. The research hypothesis was tested by using ANOVA test followed by Tukey test. These results indicate (1) learning strategy gives a significantly different influence on the result of class VIII studying biology SMP Negeri 1 Binjai (Fcount 6.110>Ftable 4.10), (2) Locus of Control gave a significantly different effect on learning outcomes Biology class VIII SMP Negeri 1 Binjai (Fcount 19.703>Ftable 7.35), (3) There is interaction between the learning strategy with the Locus of Control students on the results of class VIII studying biology SMP Negeri 1 Binjai (Fcount 6.255> 4.10 Ftable ), (4) The study of biology students in the class who have a Learning Cycle Internal Locus of Control was higher ( = 81.50) compared with students who have an External Locus of Control on Conventional class ( = 67.50), higher than students who have the Internal Locus of Control on Conventional class ( = 74.32) and higher than students who have an External Locus of Control on Conventional class ( = 70.23). Kata Kunci: Learning Cycle, Locus ofControl, IPA